Everyday Life of Accounting Disclosure – Exploring Home Accountants’ Practices in Indonesia - Wahyudi, Imam (The Indonesian Journal of Accounting Research, 2021)
Abstract: The study intends to identify the accounting practices used at home –budgeting, record keeping and the use of the information for decision making related to home affairs. Exercising exploratory research, this study using accounting academics as well as accounting practitioners as informants. Data are collected mostly from informal interviews and a focus group discussion with ten informants. All of them are peer and close friends of the researcher. The analysis is conducted manually by tracing all interview transcripts and comparing the transcripts with secondary data from the informants. The study found that accounting practices at home tend to be dominated by financial management that focuses on cash flow management. Budgeting and record keeping are addressed mostly to manage cash flows in order to avoid deficit and to make long-term investment.